Model Komunikasi Polresta dalam Penyaluran Bantuan Tunai Pedagang Kaki Lima dan Warung (BTPKLW) di Pekanbaru - Muhammad Calvin Andready (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
The distribution of cash assistance to street vendors and small shop owners (BTPKLW) is one of the efforts made by the Government to provide support to the informal sector in facing the economic impacts of the COVID-19 pandemic. One of the institutions involved in the distribution of Cash Assistance for Street Vendors and Small Shop Owners (BTPKLW) in Pekanbaru is the City Police Resort (Polresta). This study aims to analyze the communication model used by Polresta Pekanbaru in the distribution of cash assistance to BTPKLW, focusing on the Laswell communication model and the simple linear communication model with feedback. This research used a qualitative approach with data collection techniques such as observation, interviews, and documentation. The research respondents consisted of members of the Community Development Unit (Binmas) of Polresta Pekanbaru, street vendors, and small shop owners. The data analysis techniques used in this study are data reduction, presentation, and conclusions. The results of the study showed that Polresta Pekanbaru utilized various communication channels, including official websites and social media, as well as direct meetings with street vendors and small shop owners. The communicators, represented by the Binmas Unit of Polresta Pekanbaru, provided information on the requirements, schedule, and mechanism of cash assistance distribution to the vendors and shop owners. The messages conveyed by the communicators were clear and detailed. Feedback from the recipients was demonstrated through the completion of registration forms for prospective BTPKLW recipients. However, the study also identified several obstacles in the implementation of cash assistance distribution, particularly related to the verification of recipient data. These obstacles included inaccuracies in the data provided by the recipients, document authenticity, and data duplication. Based on the findings of this research, it is recommended that cash assistance recipients carefully pay attention to the information provided by the Binmas Unit of Polresta Pekanbaru, comply with the established procedures, complete the required documents accurately, ask for clarification when needed, maintain effective communication, and utilize the assistance wisely.